Geospatial Analysis of Road Traffic Accidents, Injuries and Deaths in Nigeria - Tolulope Osayomi; Abidoun Ayooluwa Areola (Indonesian Journal of Geography, 2015)
RTAs in Nigeria are very high and have become progressively important because of their heavy health and financial burden. The few geographic studies on RTAs in Nigeria are limited to their mere spatial distribution and associated risk factors, with very little attention given to their spatial clustering patterns and the detection of hotspots. With the aid of Global Moran’s I and Local Getis, the study found some evidence of significant positive spatial autocorrelation, and consistent clustering of RTAs, RTIs and RTDs in the southwest from 2002 to 2007 which suggested the presence of an accident belt in the southwestern region, which has been accounted by poor road infrastructure, relatively high level of economic development and high vehicular movements. The study recommends the deployment of road safety officials to the accident belt, strict enforcement of safety belts and helmets, and periodic road maintenance.